2020
DOI: 10.1002/jbm.a.36983
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal lncRNAs NONMMUT000375.2 and NONMMUT071578.2 derived from titanium particle treated RAW264.7 cells regulate osteogenic differentiation of MC3T3‐E1 cells

Abstract: Periprosthetic osteolysis and the subsequent aseptic loosening can lead to the failure of joint replacement. Wear particles are well known to be the initiative cause inducing osteolysis through enhancing osteoclast‐mediated bone resorption and reducing osteogenic differentiation. The purpose of this study was to investigate the effects of osteoclast‐secreted exosomal long noncoding RNAs (lncRNAs) on osteogenesis in the process of particle‐induced osteolysis. RAW264.7 cells were treated by titanium particles (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…miR-23a-5p-containing exosomes effectively inhibit Runx2 and promote Yes-associated protein-1- (YAP1-) mediated MT1DP by suppressing osteoblast differentiation. Exosomes produced by RAW 264.7 cells after titanium particle treatment inhibit the differentiation of MC3T3-E1 cells [ 100 ]. The analysis of differentially expressed lncRNAs in exosomes produced by RAW 264.7 cells revealed that lncRNA NONMMUT000375.2 and lncRNA NONMMUT071578.2 might play an essential role in inhibiting osteoblast differentiation.…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…miR-23a-5p-containing exosomes effectively inhibit Runx2 and promote Yes-associated protein-1- (YAP1-) mediated MT1DP by suppressing osteoblast differentiation. Exosomes produced by RAW 264.7 cells after titanium particle treatment inhibit the differentiation of MC3T3-E1 cells [ 100 ]. The analysis of differentially expressed lncRNAs in exosomes produced by RAW 264.7 cells revealed that lncRNA NONMMUT000375.2 and lncRNA NONMMUT071578.2 might play an essential role in inhibiting osteoblast differentiation.…”
Section: Exosomes and Bone Metabolismmentioning
confidence: 99%
“…The composition of the applied biomaterials directly affects the type and activity of the released exosomes [59]. Previous studies have confirmed that bioceramics can influence the production of specific types of exosomes in mammalian cells, which can lead to an improved tissue-healing process through the activation and enhancement of biological phenomena such as osteogenesis and angiogenesis [60][61][62][63][64]. In this regard, Lin et al showed that strontium-substituted calcium silicates (Sr-CS) can promote neovascularization through the activation of human umbilical vein endothelial cells (HUVECs) to produce and secrete proangiogenic miR-146a-containing exosomes, and the inhibition of Smad4 and NF2 proteins [65].…”
Section: Impact Of Bgs On Exosome Biogenesismentioning
confidence: 99%
“…In another study, exosomes from the macrophages treated with Titanium particles inhibited osteogenic differentiation. RNA sequencing and gene ontology studies have revealed the role of two long non-coding RNAs-NONMMUT000375.2 and NONMMUT071578.2-in suppressing osteogenesis through regulation of genes Bcl2, Wnt11, TGF-β, and Pdk1 [220]. There are also recent indications that the doping of biomaterials with certain trace elements has been shown to influence the exosome cargo of mesenchymal stem cells towards enhanced angiogenic potential.…”
Section: Role Of Biomaterials In Influencing Exosomal Cargomentioning
confidence: 99%